The Effect of Service and Satisfaction of Pregnant Women on Antenatal Visits to Midwives - Tabelak, Tirza Vivianri Isabela; Kiah, Firda Kalzum; Tadom, Nurlaelah Al (JURNAL INFO KESEHATAN, 2022)
The utilization of antenatal services for pregnant women can be determined based on the achievements of K1 (first contact) and K4 (4 times contact) during pregnancy with competent and authorized health workers. The World Health Organization asserts that the attitude and performance of health workers are an essential elements of service quality as it affects the understanding and satisfaction of women, partners, and families in seeking ANC, delivery, and postnatal services. The objective of this research is to examine the effect of antenatal care by midwives and the satisfaction of pregnant women on antenatal visits. The type of this research is analytic observational with a cross-sectional design, performed from March - June in Kupang City. The research subjects were 120 pregnant women with a gestational age of 36 weeks. Data collection employed questionnaires and MCH Handbook. The analysis conducted was univariate and bivariate by employing the Chi-square test with Alpha = 0.05. The results of the study on 120 pregnant women demonstrated that most of the pregnant women received good service (98.3%) and most of whom (60%) were satisfied with the services they experienced. Seventy-one people (59.2%) possessed complete visits. The Chi-square test results revealed relationship between service and satisfaction of pregnant women with antenatal visits (p = 0.652, p = 0.324). The majority of pregnant women had thorough consultations, received adequate antenatal care, and were pleased with the services they received. In addition to satisfaction, health services and programs must be performed in accordance with local culture and language in order to be accepted by the community, encompassing a decision-making culture that can influence pregnant women's visits to health facilities. Distance, education, profession, parity, and the husband's support can all have an impact on the mother's adherence to antenatal visits.